Progresso e moral na filosofia da história de Kant (SciELO - Editora UFABC, 2017)
Can we discern some rational pattern of historical development amid the constant back and forth of facts and events? Can we accept the idea that we human beings are constantly making progress towards a better world? On what basis and on what assumptions can we say that humanity progresses morally? Beyond the development of civilization and political institutions around the world, can we find any progress in human relations based on the principle that we should only obey laws that we establish ourselves? This book seeks to answer such questions by reconstructing the idea of ​​a philosophical history formulated by Immanuel Kant. The reader is invited to visit with us some of the main works of this author, so that we can take a stand on the subject! We add that, unlike what many manuals teach, the image that emerges here is that of a less formalistic Kant, more attentive to the conditions for the realization of reason in the world.